2013
DOI: 10.1016/j.jpeds.2013.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Height and Child Growth Patterns

Abstract: ObjectiveTo examine associations between maternal height and child growth during 4 developmental periods: intrauterine, birth to age 2 years, age 2 years to mid-childhood (MC), and MC to adulthood.Study designPooled analysis of maternal height and offspring growth using 7630 mother–child pairs from 5 birth cohorts (Brazil, Guatemala, India, the Philippines, and South Africa). We used conditional height measures that control for collinearity in height across periods. We estimated associations between maternal h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
191
1
16

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(232 citation statements)
references
References 36 publications
24
191
1
16
Order By: Relevance
“…Both maternal weight and stature may influence the linear growth potential and weight gain of the children. These circumstances have been explained by the sharing of genetic, socioeconomic and environmental characteristics (Addo et al, 2013;Araújo et al, 2010;Felisbino-Mendes et al, 2014;Figueroa Pedraza et al, 2013;Sichieri et al, 2010;Symonds et al, 2013). Current analysis revealed a strong association between birth weight and the anthropometric nutritional status of children, with similar results in previous studies, such as studies based on municipal or state population data (Jesus, Castelão, Vieira, Gomes, & Vieira, 2014;Figueiroa et al, 2012;Rissin et al, 2011) and in populations marked by social inequity Lang et al, 2011;Silveira et al, 2010).…”
Section: Discussionsupporting
confidence: 84%
“…Both maternal weight and stature may influence the linear growth potential and weight gain of the children. These circumstances have been explained by the sharing of genetic, socioeconomic and environmental characteristics (Addo et al, 2013;Araújo et al, 2010;Felisbino-Mendes et al, 2014;Figueroa Pedraza et al, 2013;Sichieri et al, 2010;Symonds et al, 2013). Current analysis revealed a strong association between birth weight and the anthropometric nutritional status of children, with similar results in previous studies, such as studies based on municipal or state population data (Jesus, Castelão, Vieira, Gomes, & Vieira, 2014;Figueiroa et al, 2012;Rissin et al, 2011) and in populations marked by social inequity Lang et al, 2011;Silveira et al, 2010).…”
Section: Discussionsupporting
confidence: 84%
“…This relationship has been reported by earlier studies. For example, in an analysis of data of 5 birth cohorts, it was established that short mothers were more likely to have a stunted child [30]. Data from other studies from countries of varying economic development have also shown this relationship [31][32][33].…”
Section: Discussionmentioning
confidence: 98%
“…that also used the PNDS data set (23) and other studies (50,51) . Mothers with short stature most likely provide a nutritionally restricted uterine environment; therefore, the fetus will have an inadequate supply of nutrients and restricted growth, which will result in low birth weight and short stature (48) .…”
Section: Discussionmentioning
confidence: 99%